Making the transition from non-native speaker to near-native speaker teachers of English: facing globalization challenges in teaching English - Mohamed Ali, Haja Mohideen (2009)
Many job advertisements seeking teachers of English to work in Japan, China, South Korea and Thailand, for instance, specify that they are looking for native speaking teachers from USA, UK, Australia and New Zealand. They do not seem to be interested even in trained non-native speaking teachers from their own countries. This situation also exists in many other countries where there is clear preference for native speaking teachers. This paper discusses the characteristics, according to scholars in language acquisition, that a native speakers can aspire to approximate to the notion of nativeness in language output. Even though the concept of a native speaker, for that of English has become somewhat subjective due to its globalized role, there are some basics that define a native speaker. A non-native speaker is generally who does not speak a particular language as his/her first language.